2000
DOI: 10.1385/ep:11:1:77
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Adenomas with Pronounced Lymphocytic Infiltration: No Evidence of Autoimmune Pathogenesis

Abstract: Pronounced lymphocytic infiltration in parathyroid adenoma is rare, with only six previously reported cases in the literature. The aims of this study are to review the features and investigate the pathogenesis of this rare entity. Two solitary parathyroid adenomas having this feature were reported, and the clinicopathologic features of all the documented cases were reviewed. The nature of the lymphoid infiltrate and the presence of Epstein-Barr virus (EBV) were analyzed to unveil the pathogenesis of this infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…These findings support the hypothesis that the adaptive immune response influences the behavior of human tumors. However, lymphocytic infiltration in parathyroid adenoma is rarely reported (27), which suggests that our current findings may represent a newly recognized histologic feature. Because we found lymphocytes in both normal and adenomatous parathyroid glands, the role of these T cells is still unclear.…”
Section: Discussionmentioning
confidence: 59%
“…These findings support the hypothesis that the adaptive immune response influences the behavior of human tumors. However, lymphocytic infiltration in parathyroid adenoma is rarely reported (27), which suggests that our current findings may represent a newly recognized histologic feature. Because we found lymphocytes in both normal and adenomatous parathyroid glands, the role of these T cells is still unclear.…”
Section: Discussionmentioning
confidence: 59%
“…Its presence is not likely to imply an autoimmune disorder. The main hypothesis is that the lesion may be a result of local tissue response [2]. Another study suggested that the histological picture is consistent with an autoimmune process directed against the adenomas, indicating that this reaction had, in part, been successful in reducing the abnormal cell population [3].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one of the patients had breast cancer and one had nodular goiter. Lam et al [8] examined one surgery-obtained parathyroid adenoma and one autopsy-obtained parathyroid adenoma and noted pronounced lymphocytic infiltration within the tumors. These authors claimed that the inflammation might have been due to local tissue response to the parathyroid adenoma.…”
Section: Introductionmentioning
confidence: 99%